Profitabilitas Dan Leverage Sebagai Pemoderasi Pengaruh Corporate Social Responsibility Pada Nilai Perusahaan - Putu Pande R. Aprilyani Dewi; Kadek Linda Kusnita (JURNAL AKUNTANSI, 2022)
This study determines the effect of the corporate social responsibility on firm value. The population of this study is composed of mining companies listed on the Indonesian Stock Exchange from 2018 to 2021. The study used a purposive sampling technique and obtained a sample of 56 companies. The results of this study indicate that corporate social responsibility has an effect on the value of mining companies. Profitability strengthens the influence of corporate social responsibility on the value of mining companies, this is because high profitability is expected to increase the value of the company. Leverage weakens the influence of corporate social responsibility on the value of mining companies, this is because leverage reflects how much the company can finance company assets which will affect the level of investor confidence in investing their shares.